Analysis of Customer Satisfaction Using the End User Computing Satisfaction Approach Toward Users of Digital Post-Payment Application Gopay Later - Sudirjo, Frans; Geertruida Bororing, Grace Martha; Harsono, Iwan; Widia Nurdiani, Tanti; Naim, Ifin (Jurnal Informasi dan Teknologi, 2024)
The purpose of this study is to identify and quantify the factors that affect consumers' satisfaction when they use pay later. This study uses a quantitative methodology. Researchers used questionnaires to get information. To pick 100 respondents from the research population, which was made up of pay later users who were actively using the service, the researchers used purposive selection approaches. Partial least squares structural equation modeling is the data analysis technique used in this study (PLS-SEM). The research findings indicated that there was a high degree of goodness and excellence in the data quality and the data outcomes acquired through the outer and inner models. All hypotheses tested in this study were accepted, indicating that the variables measured, such as content, accuracy, format, and ease of use, have a significant effect on the level of end-user satisfaction. Testing of the model structure also confirmed the acceptance of all hypotheses, with accuracy proven to have the greatest influence on ease of use. This research shows that the accuracy aspect of the use of a system or product has the most significant impact on user satisfaction. However, it is important to note that all variables, including content, format, and ease of use, also positively contribute and cannot be ignored. Therefore, even though accuracy has the greatest influence, the presence of all these factors remains an important aspect of analyzing customer satisfaction in this research.